Modernisasi Melalui Pembangunan Menuju Kesejahteraan Masyarakat Indonesia - Allya Salsa Bilatul Kh; Diajeng Anugrah Cantika Sari; Fatkurohman Nur Rangga (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Indonesia, as a developing country, faces challenges in improving people's welfare through development that is not yet optimal. Under the leadership of President Joko Widodo, the government is focusing on significant infrastructure development in an effort to encourage economic growth and modernization. Using Harrod Domar's modernization theory, this research examines how investment in infrastructure can encourage Indonesia's economic growth. The method used is literature study, with analysis of literature related to infrastructure development and modernization theory. The results show that toll road construction has a positive impact on transportation efficiency, community mobility, and economic growth, although it also faces several challenges such as environmental impacts and community involvement. The construction of toll roads, especially through collaboration between the government and the private sector, is an example of the application of Harrod Domar's theory in the context of Indonesian modernization, showing that effective investment in infrastructure can increase productivity and community welfare.